Modified PDPWM control with MPPT algorithm for equal power sharing in cascaded multilevel inverter for standalone PV system under partial shading - Mawadah Glaa Yahya; Massara Glaa Yahya (Institute of Advanced Engineering and Science, 2023)
In this paper, a modified particle swarm optimization (MPSO) based maximum power point tracking (MPPT) controller is used to track the maximum power of a PV system using DC-DC boost converter technology. To raise the PV module's input DC voltage, a DC-DC boost converter was employed. The boost converter powered the DC-AC multilevel PWM inverter, which then delivered the output AC voltage to a solitary inductive load. Cascaded multilevel inverters are often used to condition power in renewable energy applications because they are easy to use and have few parts. Ripples in the voltage of DC link capacitors cause low order harmonics and inter harmonics in the multilevel inverter's output voltage. Phase disposition pulse width modulation (PDPWM) has the fewest harmonics. The inverter cells' power delivery is not equal in this manner. In the present paper, a strategy for improving sharing of power PDPWM for photovoltaic applications is proposed. The modified PDPWM is used on a 9-level inverter where each cell is connected to a PV array running at maximum power point tracking MPPT and under partial shadowing for single phase multilevel inverters. The MATLAB/SIMULINK software was used to do simulations, and the findings demonstrate that the method presented is effective at balancing the way power is shared between different inverter cells and reducing the voltage ripple of the DC link capacitor.